2016
DOI: 10.1097/nmd.0000000000000425
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Repeated Mood Episodes in Bipolar I Disorder

Abstract: The aim of this study was to examine the association between previous mood episodes and clinical course/functioning in a community sample (NESARC). Subjects (n=909) meet DSM-IV criteria for bipolar I disorder and provided data on number of prior episode recurrences. Number of prior mood episodes was used to predict outcomes at Wave 1 and Wave 2 of the NESARC. Previous mood episodes accounted for small, but unique variance in outcomes. Recurrence was associated with poorer functioning, psychiatric and medical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“… Clinical and neurocognitive characteristics of persons with BD were predictive of work functioning over the 5-year study. Peters et al, 2016 64 Cross-sectional survey [N=909 (BD-I)] NA Multivariate models showed increases in the total number of lifetime mood episodes were associated with small, but significantly higher likelihood of permanent disability ( b =0.01) and unemployment ( b =0.01). Recurrent mood episodes and repeated depressive episodes (vs mania) were a consistent predictor of functional impairments in patients with BD-I.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Clinical and neurocognitive characteristics of persons with BD were predictive of work functioning over the 5-year study. Peters et al, 2016 64 Cross-sectional survey [N=909 (BD-I)] NA Multivariate models showed increases in the total number of lifetime mood episodes were associated with small, but significantly higher likelihood of permanent disability ( b =0.01) and unemployment ( b =0.01). Recurrent mood episodes and repeated depressive episodes (vs mania) were a consistent predictor of functional impairments in patients with BD-I.…”
Section: Resultsmentioning
confidence: 99%
“… 63 65 Moreover, an increased number of lifetime mood episodes was associated with higher likelihood of permanent disability and unemployment. 64 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 3 – 5) The frequent recurrences of bipolar disorders are associated with poorer functioning, psychiatric and medical comorbidities, and increased odds of suicidality, disability, unemployment, and re-hospitalization. 6) …”
Section: Introductionmentioning
confidence: 99%